When (dis)affections “make families”. Unspoken, lies and failures in migration trajectories, Cape Verde - Lobo, Andrea (2020)
In this article, I intend to complexify what I have been calling “making a family at a distance” by reflecting on the secrets, the unspoken, the lies, the manipulations and the failures that permeate and constitute the family social relations between emigrants and those left behind. My intention is to ask what we can learn about such relationships when we take as a starting point not the bonds of exchange, sharing and solidarity, but the formidable strategies for manipulating oneself and migratory experiences that, through secrets, lies and omissions, feed the migratory social space in which family relationships are updated. Going further, I will address how those trajectories take place, which, supposedly made for the well-being of all, often lead to suffering, ruptures and abandonment. The data I present comes from research on two islands, Ilha da Boa Vista and Ilha de Santiago. In both cases I studied in urban...